2018
DOI: 10.1038/s41467-018-03618-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signatures of NK cells suggest impaired responsiveness in HIV-1 infection and increased activity post-vaccination

Abstract: Natural killer (NK) cells limit viral replication by direct recognition of infected cells, antibody-dependent cellular cytotoxicity (ADCC), and releasing cytokines. Although growing evidence supports NK cell antiviral immunity in HIV-1 infection, further knowledge of their response is necessary. Here we show that NK cells responding to models of direct cell recognition, ADCC, and cytokine activation have unique transcriptional fingerprints. Compared with healthy volunteers, individuals with chronic HIV-1 infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 69 publications
4
52
0
Order By: Relevance
“…Here, we found high expression of mono 4-related proteins in NK cell 5 subsets, including a CD56 dim/neg subset (NK dim ). To validate these findings, we generated a transcriptomic NK-cell signature based on previous knowledge (Costanzo et al, 2018;Liberzon et al, 2011;Rieckmann et al, 2017;Subramanian et al, 2005) and calculated the signature enrichment scores across all monocyte subsets defined in map 1 (Figure 5C-D). This calculation revealed that the mono 4 subset was significantly enriched in NK-cell-specific transcripts.…”
Section: Backmapping Identifies Mono 4 As Bona Fide Cd56 Dim Nk Cellsmentioning
confidence: 93%
“…Here, we found high expression of mono 4-related proteins in NK cell 5 subsets, including a CD56 dim/neg subset (NK dim ). To validate these findings, we generated a transcriptomic NK-cell signature based on previous knowledge (Costanzo et al, 2018;Liberzon et al, 2011;Rieckmann et al, 2017;Subramanian et al, 2005) and calculated the signature enrichment scores across all monocyte subsets defined in map 1 (Figure 5C-D). This calculation revealed that the mono 4 subset was significantly enriched in NK-cell-specific transcripts.…”
Section: Backmapping Identifies Mono 4 As Bona Fide Cd56 Dim Nk Cellsmentioning
confidence: 93%
“…Also, NK cells were shown to orientate the B cell response and the underlying affinity maturation via the restriction of follicular helper T cells, a feature that is key in the generation of broadly neutralizing antibodies . NK cell functions are influenced by vaccination and infection . In addition, recent findings in mice, macaques, and humans indicate that NK cells show adaptive‐like features .…”
Section: Introductionmentioning
confidence: 99%
“…13 NK cell functions are influenced by vaccination and infection. 14,15 In addition, recent findings in mice, macaques, and humans indicate that NK cells show adaptive-like features. [16][17][18][19] However, it is not yet fully clear how these findings can be exploited to…”
mentioning
confidence: 99%
“…Conversely, the inhibitory receptor genes LILRB1, LAG3, and TIGIT were upregulated and KLRB1, LAIR2, and SIGLEC7 were down-regulated. In addition, we observed increased expression of BIRC3, TNF, and IFNG, which have been proposed to be NK cell activation markers 22 . Despite the beneficial roles of NK cells in antiviral responses, their function is known to be impaired by chronic HIV infection 60 .…”
Section: Identification Of Novel Genes Associated With T Cell Exhaustionmentioning
confidence: 65%
“…Despite the great promise of reversal of T cell exhaustion as a curative strategy for HIV, little is known about the mechanisms involved in immune cell exhaustion in HIV-infected individuals at the transcriptomic level. In addition, chronic HIV infection is associated with exhaustion not only of T cells but also of B and NK cells [20][21][22] . Therefore, it is possible that these three exhausted cell populations could cooperate in contributing to host immune system dysfunction, allowing unchecked HIV replication and disease progression.…”
mentioning
confidence: 99%